2018
DOI: 10.18203/2349-2902.isj20184631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic complications and risk factors among diabetic foot ulcer patients: a retrospective hospital-based study

Abstract: Background: Diabetic foot ulcer is a painful, demands increased health care utilization, and increases healthcare costs for the patients as well as the health care system. The purpose of this study was to analysis the prevalence of diabetic foot complications and risk factors among diabetic patients at tertiary care Hospital, Karimnagar.Methods: Total 60 sample sizes were included in the study. The study was conducted at General Surgery ward, Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar from Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This finding is in line with the results of studies conducted in Mizan Tepi, Southwest Ethiopia (36.5%) [17], and Jordan 34% [18]. However, the findings of this study are lower than those of studies conducted in Kenya, Iraq, the United Kingdom, India, Spain, and China, which found an overall prevalence of foot deformity among diabetic patients were 46% [29], 46.7% [30], 44.5% [19] , 40% [31], 60.2% [32], and 42% [33] respectively. This difference could be due to variations in the ages of study participants, study design, and assessment methods, or to differences in the study populations.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in line with the results of studies conducted in Mizan Tepi, Southwest Ethiopia (36.5%) [17], and Jordan 34% [18]. However, the findings of this study are lower than those of studies conducted in Kenya, Iraq, the United Kingdom, India, Spain, and China, which found an overall prevalence of foot deformity among diabetic patients were 46% [29], 46.7% [30], 44.5% [19] , 40% [31], 60.2% [32], and 42% [33] respectively. This difference could be due to variations in the ages of study participants, study design, and assessment methods, or to differences in the study populations.…”
Section: Discussionsupporting
confidence: 88%
“…Less than five years since the first leg surgery [5] also about 85% begins with a diabetic ulcer which then progresses to severe gangrene or disease [4]. Increasing age, especially in men, which predominates in the limbs are peripheral vascular disease, peripheral neuropathy, and kidney infection, and weight gain, unfavorable diabetes control, and longer diabetes are the determinants of death after ulceration which is the cause of the high mortality rate of diabetics [6][7][8].…”
mentioning
confidence: 99%